Overview of Pending and Dispute Events in the Health BPJS Claiming Process for Inpatients at Imelda Hospital, Medan, Indonesia in 2022 - valentina valentina; Esraida Simanjuntak; Siti Permata Sari Lubis; Linfia Isti Zenika Hulu (LPPM Hang Tuah Pekanbaru, 2023)
Health insurance is a guarantee in the form of health protection so that participants obtain health care benefits and protection in meeting basic health needs that are given to everyone who has paid contributions or whose contributions are paid by the government. The purpose of this study is to describe the implementation of the BPJS (Social Security Administering Agency) Health claim system for inpatients at Imelda Workers' Hospital in Indonesia. This type of research is qualitative with a case study approach. The method used is observation and direct interviews to the field. The subjects used in this study were all pending and disputed medical record claim files for inpatients and in March 2022 as many as 94 claim files. The informants used in this study were 3 BPJS Health claims officers. Based on the results of the study, the implementation of inpatient BPJS Health claims is in accordance with regulations and SOPs at Imelda Indonesian Workers Hospital in Medan, the obstacles in the claiming process are facilities and networks that often have problems. The claim officer will scan the inpatient file and insert it into the hard disk and send it to BPJS Kesehatan. The hospitalization files that were claimed and submitted in March 2022 were 420 files, of which 326 files were received (78%) and 94 files were rejected (pending claims) (22%). There were also 27 disputed claim files in March 2022 (29%), after the submission of pending claims was made by Imelda Indonesian Workers Hospital in Medan.